The Risk Premiumon Italian Government Debt, 1976-1988 - Cottarelli, Carlo (IMF Working Papers; Working Paper ;, 1990)
This paper considers the behavior of the yield differential between government and nongovernment bonds in Italy between 1976 and 1988. It is shown that the trend increase of the differential observed in this period was significantly influenced by the deterioration of public finances, as reflected both by an increase in the relative supply of government with respect to nongovernment paper and by a worsening of selected default risk indicators. In addition, the effect of relative supply factors was found to be statistically more robust and quantitatively more important than the effect of risk indicators in explaining the movements of the yield differential.